A Newly Identified Role of the Deciduous Forest Floor in the Timing of Green‐Up. Issue 11 (9th November 2017) - Lapenis, Andrei G.; Lawrence, Gregory B.; Buyantuev, Alexander; Jiang, Shiguo; Sullivan, Timothy J.; McDonnell, Todd C.; Bailey, Scott
Abstract: Plant phenology studies rarely consider controlling factors other than air temperature. We evaluate here the potential significance of physical and chemical properties of soil (edaphic factors) as additional important controls on phenology. More specifically, we investigate causal connections between satellite‐observed green‐up dates of small forest watersheds and soil properties in the Adirondack Mountains of New York, USA. Contrary to the findings of previous studies, where edaphic controls of spring phenology were found to be marginal, our analyses show that at least three factors manifest themselves as significant controls of seasonal patterns of variation in vegetated land surfaces observed from remote sensing: (1) thickness of the forest floor, (2) concentration of exchangeable soil potassium, and (3) soil acidity. For example, a thick forest floor appears to delay the onset of green‐up. Watersheds with elevated concentrations of potassium are associated with early surface greening. We also found that trees growing in strongly acidified watersheds demonstrate delayed green‐up dates. Overall, our work demonstrates that, at the scale of small forest watersheds, edaphic factors can explain a significant percentage of the observed spatial variation in land surface phenology that is comparable to the percentage that can be explained by climatic and landscape factors. We conclude that physical and chemical properties of forest soil play important roles in forest ecosystems as modulators of climatic drivers controlling the rate of spring soil warming and the transition of trees out of winter dormancy. Key Points: The spatial variability of green‐up days is controlled by climate as well as by physical and chemical properties of forest soil Forest floor thickness, the concentration of exchangeable potassium, and soil acidity manifest themselves as controls of surface greening Biochemical mechanism linking the forest floor and green‐up dates might be instrumental for predicting forest responses to climate warming Plain Language Summary: Plant phenology studies usually focus on air temperature. We investigated the potential significance of soil (edaphic) properties as additional important controls on phenology using satellite‐observed green‐up dates of small forested watersheds and measured soil properties in the Adirondack Mountains of New York, USA. Three factors manifest themselves as significant controls of seasonal patterns of variation in vegetated land surfaces observed from remote sensing: (1) thickness of the forest floor, (2) concentration of exchangeable soil potassium, and (3) soil acidity. A thick forest floor and acidified conditions appear to delay the onset of green‐up, whereas watersheds with elevated concentrations of potassium are associated with early surface greening. Our work demonstrates that edaphic factors can explain a significant percentage of the observed spatial variation in land surface phenology and timing of forest green‐up that is comparable to the percentage that can be explained by climatic and landscape factors. Further research on how climate change is affecting the start of the growing season will need to incorporate ecosystem factors such as these to understand the response of forests to climate trends.